Pengembangan Alat Peraga Sistem Peredaran Darah Manusia dari Barang Bekas pada Pembelajaran IPA Siswa Sekolah Dasar - Ardhi, Shahibul (Empiricism Journal, 2022)
Tujuan penelitian ini untuk mengetahui bagaimana pengembangan alat peraga sistem peredaran darah manusia dari barang bekas pada pembelajaran IPA siswa Sekolah Dasar Kelas V Tahun Pelajaran 2021/2022. Jenis penelitian ini adalah penelitian dan pengembangan (Research and Development) menggunakan model desain pengembangan 4D. Teknik pengumpulan data dalam penelitian ini menggunakan angket lembar validasi ahli. Teknik analisis data dalam penelitian ini dianalisis secara deskriptif dengan interval kevalidan yang telah ditentukan. Hasil analisis data menunjukkan bahwa Media pembelajaran yang dikembangkan layak digunakan sebagai media pembelajaran, dimana hasil validasi ahli materi memperoleh skor rata-rata yaitu 90,2% dengan kriteria sangat valid dan ahli media memperoleh skor rata-rata 85,7% dengan kriteria sangat valid. Development of Teaching Aids for the Human Circulatory System from Used Goods in Learning Science for Elementary School Students Abstract The purpose of this study was to find out how to develop teaching aids for the human circulatory system from used goods in learning science for elementary school students in Class V for the 2021/2022 academic year. This type of research is research and development (Research and Development) using the 4D development design model. The data collection technique in this study used an expert validation sheet questionnaire. Data analysis techniques in this study were analyzed descriptively with predetermined validity intervals. The results of data analysis show that the developed learning media is suitable for use as learning media, where the validation results of material experts obtain an average score of 90.2% with very valid criteria and media experts obtain an average score of 85.7% with very valid criteria.